On three new high-altitude endemic leiodids (Coleoptera: Leiodidae) from the Balkan Peninsula - Ćurčić, Srećko; Ćurčić, Božidar; Makarov, Slobodan; Mitić, Bojan; Mihajlova, Branislava (Entomologica Fennica, 2005)
Three new leiodid beetle species, viz. Petkovskiella henrikenghoffi sp. n. (Republic of Macedonia, Mt. Dautica), Babuniella jovanhadzii sp. n. (Republic of Macedonia, Mt. Karadžica) and Magdelainella milojebrajkovici sp. n. (Serbia, Mt. Javor), are described and diagnostified. Both adult genitalia and other taxonomically important characters are illustrated. Babuniella Z. Karaman is given a full generic status. All new species studied are clearly distinct from their closest congeners. These forms are of the Tertiary or even pre-Tertiary origin and age, and represent both relicts and endemics inhabiting central and southern areas of the Balkan Peninsula.